Temperate Phages Acquire DNA from Defective Prophages by Relaxed Homologous Recombination: The Role of Rad52-Like Recombinases - De Paepe, Marianne; Hutinet, Geoffrey; Son, Olivier; Amarir-Bouhram, Jihane; Schbath, Sophie; Petit, Marie-Agnès (PLoS genetics, 2014)
Bacteriophages (or phages) dominate the biosphere both numerically and in terms of genetic diversity. In particular, genomic comparisons suggest a remarkable level of horizontal gene transfer among temperate phages, favoring a high evolution rate. Molecular mechanisms of this pervasive mosaicism are mostly unknown. One hypothesis is that phage encoded recombinases are key players in these horizontal transfers, thanks to their high efficiency and low fidelity. Here, we associate two complementary in vivo assays and a bioinformatics analysis to address the role of phage encoded recombinases in genomic mosaicism. The first assay allowed determining the genetic determinants of mosaic formation between lambdoid phages and Escherichia coli prophage remnants. In the second assay, recombination was monitored between sequences on phage λ, and allowed to compare the performance of three different Rad52-like recombinases on the same substrate. We also addressed the importance of homologous recombination in phage evolution by a genomic comparison of 84 E. coli virulent and temperate phages or prophages. We demonstrate that mosaics are mainly generated by homology-driven mechanisms that tolerate high substrate divergence. We show that phage encoded Rad52-like recombinases act independently of RecA, and that they are relatively more efficient when the exchanged fragments are divergent. We also show that accessory phage genes orf and rap contribute to mosaicism. A bioinformatics analysis strengthens our experimental results by showing that homologous recombination left traces in temperate phage genomes at the borders of recently exchanged fragments. We found no evidence of exchanges between virulent and temperate phages of E. coli. Altogether, our results demonstrate that Rad52-like recombinases promote gene shuffling among temperate phages, accelerating their evolution. This mechanism may prove to be more general, as other mobile genetic elements such as ICE encode Rad52-like functions, and play an important role in bacterial evolution itself.